Ideas and Images from Argentina. - Glusberg, Jorge (Jyvaskyla : The Alvar Aalto - Museum, 1987)
Alvaro, Jorge ; Lopez, Gustavo ; Audivert, Eduardo ; Bedel, Jacques ; Benedit, Luis Fernando ; Benguria, Silvina ; Bertani, Ernesto ; Bobbio, Pablo ; Burton, Mildred ; Cambre, Juan José ; Castilla, Americo ; Dobarro, Nora ; Eckell, Ana ; Esteves, Mercedes ; Fazzolari, Fernando ; Faunes, Daniel ; Lublin, Lea ; Medici, Hector ; Minujin, Marta ; Monzo, Osvaldo ; Paksa, Margarita ; Paparella, Aldo ; Paz, Hilda ; Pereya, Luis ; Pierri, Duilio ; Poli, Yanz ; Portillos, Alfredo ; Prior, Alfredo ; Rearte, Armando ; Renzi, Juan Pablo ; Romberg, Osvaldo ; Soibelman, Elsa ; Testa, Clorindo ; Peralta Urquiza, Wells, Luis ; Zamora, Argentina ; Zelaya, Daniel
Ideas and Images from Argentina, The Alvar Aalto - Museum, Jyvaskyla, 14.5. - 14.6.1987
boek
Keywords: Argentinië